Adaptive Stabilization of Some Multivariable Systems with Nonsquare Gain Matrices of Full Rank - Zhiteckii, L.S.; Solovchuk, K.Yu. (Кибернетика и вычислительная техника, 2018)
The purpose of this paper is to answer the question of how the pseudoinverse modelbased adaptive approach might be utilized to deal with the uncertain multivariable memoryless system if the number of control inputs is less than the number of outputs. Results. It is shown that the parameter estimates generated by the standard adaptive projection recursive procedure converge always to some finite values for any initial values of system’s parameters. Based on these ultimate features, it is proved that the adaptive pseudoinverse model-based control law makes it possible to achieve the equilibrium state of the nonsquare system to be controlled. The asymptotical properties of the adaptive feedback control system derived theoretically are substantiated by a simulation experiment.